Studies on variability, correlation coefficient and path analysis for yield associated traits in soybean [Glycine max (L.) Merrill]: STUDIES ON VARIABILITY, CORRELATION COEFFICIENT AND PATH ANALYSIS FOR YIELD IN SOYBEAN - SHRISHTI MEHRA; M K SHRIVASTAVA; PAWAN K AMRATE; R B YADAV (Journal of Oilseeds Research, 2020)
In the present study, genotypic and phenotypic variability, correlation coefficient and path analysis were worked out on forty six important soybean genotypes for yield and its attributing characters at JNKVV, Jabalpur. The highest per cent of PCV (37.69), GCV (37.48) and heritability (98.9) were found for number of pods/plant. The number of pods/plant was significantly correlated with number ofseeds (0.7595) and seed yield/plant (0.6316). Path coefficient analysis also revealed, substantially higher positive direct effects of number of pods/plant (0.8364) and number of seeds/pod (0.5177) on seed yield/plant.